2005
DOI: 10.1063/1.2034101
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated diamond nanorods, the densest and least compressible form of carbon

Abstract: We report the synthesis of aggregated diamond nanorods (ADNRs) from fullerene C60 at 20(1) GPa and 2200  °C using a multianvil apparatus. Individual diamond nanoroads are of 5–20 nm in diameter and longer than 1μm. The x-ray and measured density of ADNRs is ∼0.2%–0.4% higher than that of usual diamond. The extremely high isothermal bulk modulus KT=491(3)GPa [compare to KT=442(4)GPa of diamond] was obtained by in situ x-ray diffraction study. Thus, ADNRs is the densest among all carbon materials and it has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 19 publications
2
68
0
5
Order By: Relevance
“…Hence, any data obtained for small-sized, poorly crystallized samples have to be considered invalid. For example, the statement that a diamond nanorods composite has the bulk modulus B ~ 490 GPa, which is 11% greater than the value for diamond [45], is obviously untrue. Undoubtedly erroneous is information on record high bulk moduli of carbon phases obtained from fullerite C 60 : B ~1000 -1600 GPa [46].…”
Section: Superhard Materials: More Equal Than Othersmentioning
confidence: 99%
“…Hence, any data obtained for small-sized, poorly crystallized samples have to be considered invalid. For example, the statement that a diamond nanorods composite has the bulk modulus B ~ 490 GPa, which is 11% greater than the value for diamond [45], is obviously untrue. Undoubtedly erroneous is information on record high bulk moduli of carbon phases obtained from fullerite C 60 : B ~1000 -1600 GPa [46].…”
Section: Superhard Materials: More Equal Than Othersmentioning
confidence: 99%
“…[19,20] We found that, for the high frequency broad band, the most intense peak is at 1470 cm -1 when excited by an 830 nm laser, while it becomes 1540 cm -1 when using 514 nm excitation. From in situ high pressure Raman measurements, we can clearly see that the two bands at 1470 cm -1 and 1540 cm -1 evolve from the H g (7) and H g (8) modes, respectively. This is important evidence for the preservation of fullerenes or fullerenelike fragments, consisting of hexagonal and pentagonal carbon rings, in the high pressure phase and in the quenched sample released from 44 GPa.…”
mentioning
confidence: 99%
“…Thanks to the strong C-C covalent bonds, many carbon phases, including both crystalline and noncrystalline forms, are found to exhibit high hardness and have important technological applications in different fields. The structures and the formation mechanisms of hard carbon phases thus have been subjected to numerous experimental [1][2][3][4][5][6][7][8][9] and theoretical [10,11] works.…”
mentioning
confidence: 99%
“…1 Moreover, in the past few years, it has been possible to produce materials with very small diamond crystals, with particle sizes in the order of a few nm. 2 Indeed, the synthesis of nanocrystalline films of diamondlike carbon, polycrystalline cubic diamond, and aggregated diamond nanorods has been reported in literature [3][4][5][6][7][8][9] Importantly, polycrystalline diamond, reported to consist of very fine granular crystals, was found to be as hard or even harder than single-crystal diamond, with constant hardness throughout the sample. 3 The aggregated diamond nanorods, and mesoporous diamond composed of interconnected nanocrystals, were found to be the densest among all carbon materials and had the lowest experimentally determined compressibility.…”
Section: Introductionmentioning
confidence: 99%
“…3 The aggregated diamond nanorods, and mesoporous diamond composed of interconnected nanocrystals, were found to be the densest among all carbon materials and had the lowest experimentally determined compressibility. 8 In such polycrystalline aggregates, the amount of substance located in between the crystallites, i.e., in the grain boundary (GB), becomes considerably larger and hence very important for the material properties. Diamond GBs have therefore been studied extensively, both experimentally 2 and theoretically, [10][11][12] with substantial attention given to the determination of their chemical bonding.…”
Section: Introductionmentioning
confidence: 99%